2021
DOI: 10.3390/jcm10020176
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Its Associations with Dental Status: Data from the Dental, Oral, Medical Epidemiological (DOME) Nationwide Records-Based Study

Abstract: Conflicting results have been published regarding the associations between dental status and hypertension. This study aims to explore whether or not hypertension is associated with dental status among young to middle-aged adults. To that end, data from the Dental, Oral, Medical Epidemiological (DOME) study were analyzed. The DOME is a cross-sectional records-based study that combines comprehensive socio-demographic, medical, and dental databases of a nationally representative sample of military personnel. Incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 59 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…Moreover, findings from the Atherosclerosis Risk in Communities (ARIC) study did not support an independent association between endodontic treatment and the development of coronary heart disease, ischemic stroke, heart failure, or venous thromboembolism [22]. In our previous publications exploring the associations of MetS with periodontitis [11] and with caries [12,20], we have shown that the associations between dental pathologies and MetS components were only found in the univariate analyses, and they vanished following the multivariate analysis.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Moreover, findings from the Atherosclerosis Risk in Communities (ARIC) study did not support an independent association between endodontic treatment and the development of coronary heart disease, ischemic stroke, heart failure, or venous thromboembolism [22]. In our previous publications exploring the associations of MetS with periodontitis [11] and with caries [12,20], we have shown that the associations between dental pathologies and MetS components were only found in the univariate analyses, and they vanished following the multivariate analysis.…”
Section: Introductionmentioning
confidence: 78%
“…The current research is part of the Dental, Oral, Medical Epidemiological (DOME) crosssectional record-based nationwide study [12,20,32,33]. The protocol and study methods of the DOME study have been detailed previously [33].…”
Section: Data Sourcementioning
confidence: 99%
See 3 more Smart Citations